'Working memory is a distributed dynamic process'. Issue 3 (2nd October 2022) - Courtney, Susan M.
ABSTRACT: I propose working memory be considered, not as a process for static maintenance in a particular set of brain regions, but rather as a dynamic process unfolding to serve future needs. Brain regions such as the hippocampus, or sensory and motor regions, may be necessarily recruited during this process, depending on task demands. Information stored in working memory is thus a distributed representation reflected in the structural and functional state of multiple brain areas and the trajectory of that state over time. Recent research is discussed in support of this view.